On Behalf of the People: The Use of Public Opinion and the Perception of "the People" in Political Communication Strategies of Dutch MPs. (January 2020) - Strikovic, Edina; van der Meer, Toni G. L. A.; van der Goot, Emma; Bos, Linda; Vliegenthart, Rens
This study investigates the role of public opinion for members of parliaments (MPs) in a time in which communication about the will of "the People" is high on the political agenda. By means of face-to-face elite interviews with Dutch MPs, we explore who politicians perceive as "the People, " how they assess "the will of the People, " and how this translates into their communication strategies. We find that MPs distinguish between listening to individual opinion, to understand what topics are at the forefront of "the People's" minds, and taking political action considering a more general public. MPs are divided in their acceptance of the term "the People"—some find it useful, while others voice concerns over its antipluralistic implications. We find evidence of populist communication strategies in the form of references to public opinion across the political spectrum. Political communication is used for political marketing and to connect to the electorate. We conclude that Dutch MPs are not becoming more populist across the political spectrum, but rather that there is a tendency toward personalization and authenticity in political communication, which makes "normal" political communication appear more populist.